An explanatory study on defects in plastic molding parts caused by machine parameters in injection molding process. (2023) - Mourya, Ankush; Nanda, Arshit; Parashar, Kartik; Sushant,; Kumar, Rajender
Abstract: In the Injection Molding process, the output product quality is dependence on various attributes such as product geometry, the material used for manufacturing, and the machining parameters (process parameters). Here it is an exaggeration to say that the parameters associated with the molding process play a crucial role in the production of high-quality products. In the present study, the causal approach is used to recognize the problems associated with the injection molding components to cause defects such as shrinkage, flow lines, sink marks, burn marks, short shots, warpage, etc. This study aims to reveal the basic understanding of the injection molding process and the importance of machining parameters in moldings. This study will brief the type of defects and their causing machining parameters to the industrial practitioners/researchers. In addition, the study will suggest the parameters to set out on the machine so that the final product will be free from any defect.